Investigation the Cytotoxic and Antimicrobial Effect of Ranunculus Poluninii - Menevşe, İrem Nur; Taskin, Irmak Icen; Sancar, Pelin Yılmaz; Kurşat, Murat (My University, 2024)
Ranunculus plant species, one of the endemic plants, are used in the treatment of various diseases such as febrile diseases, rheumatism and inflammatory rashes due to their pharmacological and toxicological activities. Considering these features, it was aimed to investigate the cytotoxic effects of Ranunculus poluninii on cancer cell lines, bacteria and yeasts. For this purpose, the extract of the plant was obtained by methanol extraction. Different concentrations of stock were prepared from this plant and applied to A549 and HCT116 cancer cell lines, and MTT assay was performed to determine cell viability. In addition, MIC values were determined by applying the prepared plant extract to Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus, Candida albicans and Candida glabrata. Our results showed that Ranunculus poluninii was reduced cell viability to 83.7% at 100 µg/mL and 79% at 200 µg/mL on A549 and HCT116 respectively. In addition, it decreased both Candida albicans and Candida glabrata growth to 91.5% at 800 µg/m and 95.1% at 50 µg/mL respectively. Our results suggest that Ranunculus poluninii has anticancer effect and antifungal activity.
Keywords: MTT; MIC; : Antimicrobial; cytotoxic; Ranunculus poluninii